Deconstruction of the Meaning of Human Creation in Surah Al-Mu'minun [23]: 12–14 thru Fazlur Rahman's Hermeneutics and a Methodological Review of Tafsir Jawhari and Al-Najjar - Indah Purnama Sari; Khairunnas Jamal; Mochammad Novendri S (Global Action and Education for Society, 2025)
The development of modern science has opened new spaces for dialogue between science and religion, including within Qur’anic exegesis. QS. al-Mu’minūn [23]: 12–14 is often referenced in embryological studies because it contains a description of human creation that appears consistent with modern biological processes. The main problem of this study lies in two aspects: the application of Fazlur Rahman’s hermeneutics through the Double Movement theory in understanding contemporary interpretations, and the identification of methodological limitations when the scientific approach is used dominantly by Tantāwī al-Jawharī and Zaghlūl al-Najjār. The purpose of this research is to examine the balance between scientific, moral, and spiritual dimensions in both interpretations. This study employs a qualitative method with a library research approach, analyzing the text, historical context, and its relevance to modern scientific understanding. The results indicate that al-Jawharī emphasizes the spiritual and moral aspects of scientific interpretation, viewing science as a means to strengthen faith, whereas al-Najjār highlights empirical aspects and the scientific miracle (iʿjāz ʿilmī). Through Rahman’s hermeneutical framework, both demonstrate a serious effort to bridge revelation and science, yet methodological limitations arise when Qur’anic meanings are overly adjusted to scientific theories. This study concludes that the application of the Double Movement theory helps to position scientific interpretation proportionally so that the spiritual and moral meanings of the Qur’an remain preserved amid the dynamics of modern scientific development.